2013
DOI: 10.1002/ccd.25085
|View full text |Cite
|
Sign up to set email alerts
|

Functional diagnosis of coronary stenoses using pressure drop coefficient: A pilot study in humans

Abstract: CDP, a nondimensional parameter combining simultaneous measurements of pressure drop and velocity data, can accurately define the severity of coronary stenoses and could prove advantageous clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Based on fluid mechanics fundamentals, pressure drop is linearly correlated with flow in vessels with mild stenosis severity, whereas it is a quadratic function of flow for significant lesions. Based on this concept, the new diagnostic endpoints were mainly defined by scaling translesional pressure drop with either linear or quadratic forms of flow (14)(15)(16)(17). These new parameters have been shown to provide better delineation of stenosis severity, microvascular diseases, multiple coronary stenoses, etc.…”
mentioning
confidence: 99%
“…Based on fluid mechanics fundamentals, pressure drop is linearly correlated with flow in vessels with mild stenosis severity, whereas it is a quadratic function of flow for significant lesions. Based on this concept, the new diagnostic endpoints were mainly defined by scaling translesional pressure drop with either linear or quadratic forms of flow (14)(15)(16)(17). These new parameters have been shown to provide better delineation of stenosis severity, microvascular diseases, multiple coronary stenoses, etc.…”
mentioning
confidence: 99%
“…In general, as the severity of a single stenosis was varied, CDP was shown to change by a few orders (range: 0-1000) of magnitude [21,49,51,52]. Furthermore, CDP was shown to delineate the severity of epicardial stenosis under a clinical setting [25]. In the presence of a serial downstream stenosis, CDP values showed no specific trend or relative variation for the upstream severe stenosis, while the values for the upstream mild and intermediate stenosis showed an insignificant increasing trend with the increase in downstream severity, when evaluated under C1 condition.…”
Section: Discussionmentioning
confidence: 98%
“…Simultaneous measurements of functional parameters (pressure drop and proximal velocity), necessary for the evaluation of CDP, can be readily obtained during routine cardiac catheterization procedures using a dual-sensor tipped guidewire, also known as a combowire [23][24][25][26][27]. CDP has been validated in pre-clinical trials [21,23,24,26,27] and under a clinical setting [25], in order to delineate epicardial stenoses. Furthermore, it has been shown to be independent of heart rate [24,26] and contractility [27,28] in recently conducted in vivo animal studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDP was validated in in vitro , and in vivo animal studies to differentiate between epicardial stenosis and microvascular dysfunction. Further, in a recent pilot clinical study CDP has been shown in a patient population to distinguish between degrees of stenosis severity.…”
Section: Introductionmentioning
confidence: 99%